2017
DOI: 10.1097/olq.0000000000000662
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Human Immunodeficiency Virus and Sexually Transmitted Infections Among Cisgender and Transgender Women Sex Workers in Greater Kuala Lumpur, Malaysia: Results From a Respondent-Driven Sampling Study

Abstract: Background Sex workers face a disproportionate burden of HIV and sexually transmitted infections (STI) worldwide. For cisgender women sex workers (CWSW), global HIV prevalence is over 10%, while transgender women sex workers (TWSW) face an HIV burden of 19%–27%. Methods We used respondent-driven sampling to recruit 492 sex workers, including CWSW (n=299) and TWSW (n=193) in Greater Kuala Lumpur, Malaysia. Participants completed an in-depth survey and were screened for HIV, syphilis, Chlamydia trachomatis, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 27 publications
1
46
1
Order By: Relevance
“…This review includes 25 studies that met our inclusion criteria. 7,10,11, Details regarding these studies and their characteristics can be seen in Table 1. The size of studies, including transgender women, varied from 63 to 13,154 people (median, 786) and those including transgender men ranged from 25 to 2364 people (median, 336).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This review includes 25 studies that met our inclusion criteria. 7,10,11, Details regarding these studies and their characteristics can be seen in Table 1. The size of studies, including transgender women, varied from 63 to 13,154 people (median, 786) and those including transgender men ranged from 25 to 2364 people (median, 336).…”
Section: Resultsmentioning
confidence: 99%
“…four were focused on commercial sex workers. 7,42,47,48 In fact, of the studies investigating transgender women, 4 (16%) exclusively evaluated commercial sex workers. Research involving transgender populations has moved away from grouping commercial sex workers and transgender women into the same study population, with most of these studies being conducted in 2013 or earlier.…”
Section: Stis/hiv In Transgender Men and Womenmentioning
confidence: 99%
See 2 more Smart Citations
“…98 Recently published estimates of urogenital gonorrhoea positivity among STI clinic attending-female SWs (FSWs) range from 2.7% among women in England in 2011 (n = 2534) to 21.2% among those in Guatemala in 2012 (n = 3213). 25,[99][100][101][102][103] Data on prevalence of rectal and pharyngeal gonorrhoea among FSWs are sparse, but a large retrospective cohort study of 18 475 FSWs attending 42 sexual health clinics in Australia during 2009-15 reported an overall incidence of urogenital gonorrhoea of 1.4 per 100 PY, pharyngeal gonorrhoea was 3.6 per 100 PY, and rectal gonorrhoea was 0.3 per 100 PY. 104 The annual incidence of each increased during the analytic period, including from 1.6 per 100 PY in 2009 to 4.9 per 100 PY in 2015 for pharyngeal gonorrhoea.…”
Section: Sex Workersmentioning
confidence: 99%